Ancestral cultures of the lower basin of the Santiago River, an approach from the Apinkras Creek, in Villa Gonzalo (district of Río Santiago, Condorcanqui-Amazonas) - Villar Quintana, Anthony Alex (2024)
In this research we dive into an area scarcely known by Amazonian and Peruvian archaeology, the Kanu sor Santiago River basin, the border area between the Sub-Andean Zone and the Amazonian plain. Through the recognition of an archaeological site in Apinkras Creek, current territory of the Wampis community of Villa Gonzalo (district of Río Santiago, Condorcanqui-Amazonas) and a subsequent analysis of the associated cultural material, we seek to approach the antiquity and the characterization of the societies that elaborated these objects during their permanence in the area. In this way, we identified that our study area was situated within a large area of interaction, mainly in the Amazon, at dates not yet precisely identified, but l estimated to have occurred between 2000 BC and 400 AD.